2022
DOI: 10.21203/rs.3.rs-2252278/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of the membrane repair protein annexin-A2 prevents tumour invasion and metastasis

Abstract: Cancer cells are exposed to major compressive and shearing forces during invasion and metastasis, leading to extensive plasma membrane damage. To survive this mechanical stress, they need to repair membrane injury efficiently. Targeting the membrane repair machinery is thus potentially a new way to prevent invasion and metastasis. We show here that annexin-A2 (ANXA2) is required for membrane repair in MDA-MB-231 cells, a highly invasive triple-negative breast cancer cell line. Mechanistically, we show by fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
(49 reference statements)
2
2
0
Order By: Relevance
“…45 This has recently led to the concept that acute membrane repair might also be centrally involved in the cascade of essential mechanisms required in metastasis and resistance to cytotoxic immune cells. 46,47 Our observations that ANXA4 is modulating membrane repair of renal carcinoma cells (Figure 3), is in line with previous studies investigating the general capacity of annexin proteins to reseal and repair damaged plasma membranes (including ANXA6, ANXA5 and ANXA2). 46,48,49 Remarkably, the potential of ANXA4 for membrane repair appears not to be limited to cancer cells, as it was recently demonstrated that ANXA4 is also involved in the pathogenesis of glaucoma via mediating modes of membrane repair under biophysical strain conditions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…45 This has recently led to the concept that acute membrane repair might also be centrally involved in the cascade of essential mechanisms required in metastasis and resistance to cytotoxic immune cells. 46,47 Our observations that ANXA4 is modulating membrane repair of renal carcinoma cells (Figure 3), is in line with previous studies investigating the general capacity of annexin proteins to reseal and repair damaged plasma membranes (including ANXA6, ANXA5 and ANXA2). 46,48,49 Remarkably, the potential of ANXA4 for membrane repair appears not to be limited to cancer cells, as it was recently demonstrated that ANXA4 is also involved in the pathogenesis of glaucoma via mediating modes of membrane repair under biophysical strain conditions.…”
Section: Discussionsupporting
confidence: 91%
“…46,47 Our observations that ANXA4 is modulating membrane repair of renal carcinoma cells (Figure 3), is in line with previous studies investigating the general capacity of annexin proteins to reseal and repair damaged plasma membranes (including ANXA6, ANXA5 and ANXA2). 46,48,49 Remarkably, the potential of ANXA4 for membrane repair appears not to be limited to cancer cells, as it was recently demonstrated that ANXA4 is also involved in the pathogenesis of glaucoma via mediating modes of membrane repair under biophysical strain conditions. 50 Thereby, these observations complete our understanding of the general involvement of ANXA4 in the process of membrane repair, and further demonstrate the versatile localization modes related to extracellular and tumor inherent features.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibiting membrane repair of cancer cells with therapeutic antibodies would be a good option since it has been shown that a monoclonal anti‐ANXA6 antibody significantly decreases the invasiveness of pancreatic, lung, and breast cancer cells in vitro (O'Sullivan et al., 2017). In addition, we and other have shown that anti‐ANXA2 antibodies may affect membrane repair in cancer cells and prevent tumor growth and metastasis (Gounou et al., 2022; Lokman et al., 2013). Mechanistically, we hypothesize that antibodies enter the cell at sites of membrane damage and interfere with the membrane repair machinery.…”
Section: Discussionmentioning
confidence: 90%
“…Nevertheless, they contradict a previous study of Vila de Muga et al., in which it was reported that ANXA6 expression is lower in ER‐negative compared ER‐positive breast cancer cell lines (Vilá de Muga et al., 2009). Interestingly, we recently reported that ANXA1 and ANXA2 were also expressed at higher level in MDA‐MB‐231 compared to MCF7 cells (Gounou et al., 2022), suggesting that stronger invasive properties were associated with higher expression of membrane repair proteins. Nevertheless, we could not rule out the possibility that another cell process, such as cell growth, proliferation, motility, or lipid/glucose homeostasis, may be dysregulated and explain modified invasiveness (Grewal et al., 2021).…”
Section: Resultsmentioning
confidence: 97%